Verification of MATLAB/Simulink Power Cable Modelling with Experimental Analysis - Tze Mei Kuan; Suhaila Sulaiman; Azrul Mohd. Ariffin; Wan Mohamad Shakir Wan Shamsuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Cross-linked polyethylene (XLPE) power cable is commonly used as the medium for transmitting power supply in the power system network. However, frequent exposure of XLPE cable to the high voltage causes its insulation to degrade over time leading to electricity outages. Degradation of cable can be prevented if regular maintenance is performed using the accurate assessment method. This study models and simulates a cable system comprising of three cable sections connected by two un-degraded cable joints. This model aims to assess defect along the tested cable with the application of time domain reflectometry (TDR) technique. A series of simulations are conducted by varying the cable insulation condition to study its influence on the cable joint reflection. These simulation results from MATLAB/Simulink are validated against the actual TDR experimental results. The identical results shown between the simulation and experimental results indicate that the cable model is valid and can be used to assess the condition of a cable.